Sequential bilateral chronic calf compartment syndrome in a non-athletic patient: A case report - Zavier Yongxuan Lim; Vikaesh Moorthy; Lester Teong Jin Tan (Journal of Orthopaedic Reports)
Chronic compartment syndrome is an underdiagnosed cause of leg pain primarily seen secondary to exertion in athletic patients, with risk factors including anabolic steroid use. We report a rare case of a patient with non-athletic, non-exertional sequential bilateral calf chronic compartment syndrome with excellent recovery following bilateral fasciotomy in a 52-year old Chinese gentleman with poorly controlled diabetes.He underwent fasciotomy of the left lower limb with excellent symptomatic improvement postoperatively. Two years later, he re-presented with right calf pain and increase in right calf circumference. He then underwent right lower limb fasciotomy with complete resolution of pain subsequently.Overall, there is limited literature available regarding non-exertional chronic compartment syndrome. The present report suggests that a high degree of clinical suspicion of chronic compartment syndrome is needed in patients with poorly controlled diabetes and cardinal symptoms such as pain, tightness and cramping. Fasciotomy is an effective treatment option for chronic compartment syndrome, and should be considered even in non-athletic and non-exertional cases.